2017
DOI: 10.1093/jac/dkx286
|View full text |Cite|
|
Sign up to set email alerts
|

mcr-1 and mcr-2 (mcr-6.1) variant genes identified in Moraxella species isolated from pigs in Great Britain from 2014 to 2015

Abstract: Our results add further evidence for the mobilization of the mcr-pap2 unit from Moraxella via composite transposons leading to its global dissemination. The presence of mcr-pap2 from recent Moraxella isolates indicates they may comprise a reservoir for mcr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
119
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(124 citation statements)
references
References 19 publications
2
119
0
3
Order By: Relevance
“…Whereas feces are most commonly considered as the major factor in the transfer and spread of the mcr genes, our data showing significantly higher mcr prevalences in nasal/oropharyngeal swabs than in anal/cloacal swabs suggests that both saliva and respiratory secretions might also play important roles. The identification of mcr variants in Moraxella species ( mcr-1 and mcr-2 ) 21,29,30 and Aeromonas veronii ( mcr-3 ) 24 indicates there are organisms outside the Enterobacteriaceae that contribute to colistin resistance and these might be responsible for the differences in prevalences that we found.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Whereas feces are most commonly considered as the major factor in the transfer and spread of the mcr genes, our data showing significantly higher mcr prevalences in nasal/oropharyngeal swabs than in anal/cloacal swabs suggests that both saliva and respiratory secretions might also play important roles. The identification of mcr variants in Moraxella species ( mcr-1 and mcr-2 ) 21,29,30 and Aeromonas veronii ( mcr-3 ) 24 indicates there are organisms outside the Enterobacteriaceae that contribute to colistin resistance and these might be responsible for the differences in prevalences that we found.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies have shown the mcr-1 , mcr-2 and mcr-3 can be on plasmids in Enterobacteriaceae and chromosomes in Moraxella spp. 21,29,30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years colistin resistance has increased among pig Enterobacteriaceae isolates (Rhouma et al., ) and in the last two decades its importance in human medicine has grown, despite its potential for nephrotoxicity, as a treatment for increasingly intractable gram‐negative multiresistant infections (Falagas & Rafailidis, ; WHO, , p. 41). Recently, plasmid‐borne resistance to colistin has been identified among some Enterobacteriaceae from human and farming sources (Rebelo et al., ; Rhouma et al., ), with organisms of the genus Moraxella being a suspected source of the mobilized mcr resistance genes (AbuOun et al., ). Furthermore, transmission between pigs and humans of E. coli carrying mobile mcr genes has been documented (Olaitan et al., ).…”
Section: Introductionmentioning
confidence: 99%